Communicating Chaplains' Care: Narrative Documentation in a Neuroscience-Spine Intensive Care Unit. Issue 4 (1st October 2016) - Johnson, Rebecca; Wirpsa, M. Jeanne; Boyken, Lara; Sakumoto, Matthew; Handzo, George; Kho, Abel; Emanuel, Linda
Abstract : Chaplaincy care is different for every patient; a growing challenge is to ensure that electronic health records function to support personalized care. While ICU health care teams have advanced clinical practice guidelines to identify and integrate relevant aspects of the patient's story into whole person care, recommendations for documentation are rare. This qualitative study of over 400 free-text EHR notes offers unique insight into current use of free-text documentation in ICU by six chaplains integrated into the healthcare team. Our research provides insight into the phenomena chaplains record in the electronic record. Content analysis shows recurrent report of patient and family practices, beliefs, coping mechanisms, concerns, emotional resources and needs, family and faith support, medical decision making and medical communications. These findings are important for health care team discussions of factors deemed essential to whole person care in ICUs, and, by extension have the potential to support the development of EHR designs that aim to advance personalized care.